Assessment of toxicological potential of sodium carboxymethyl beta-glucan, a novel beta-glucan - Preece, Kayla E.; Glávits, Róbert; Murbach, Timothy S.; Endres, John R.; Hirka, Gábor; Vértesi, Adél; Szakonyiné, Ilona Pasics (Food and chemical toxicology, 2021)
In this experimental work, sodium carboxymethyl beta-glucan (CMBG), a chemically altered beta-glucan, is evaluated for mutagenicity and sub-acute oral toxicity. Specifically, the tested material was CM-Glucan Nu, a food grade powder ≥90% CMBG derived from Saccharomyces cerevisiae. A bacterial reverse mutation test was performed and resulted in no mutagenicity. A 28-day, repeated-dose, oral (gavage) toxicity test on rats was performed at dose levels of 0, 500, 1000, and 2000 mg/kg bw/day. No mortality, target organs or other treatment related effects were observed. The no observed adverse effect level (NOAEL) was 2000 mg/kg bw/day, the highest dose tested, for both male and female Han:WIST rats. •Sodium carboxymethyl beta-glucan is without mutagenicity under the experimental conditions applied.•The no observed adverse effect level of an OECD, 28-day toxicological study was 2000 mg/kg bw/day.•The findings contribute to the safety evaluation of carboxymethyl beta-glucan.